2015
DOI: 10.1039/c5cy00437c
|View full text |Cite
|
Sign up to set email alerts
|

Surface synergistic effect in well-dispersed Cu/MgO catalysts for highly efficient vapor-phase hydrogenation of carbonyl compounds

Abstract: The highly efficient vapor-phase selective hydrogenation of carbonyl compounds (e.g. furfural (FAL) and dimethyl 1,4-cyclohexane dicarboxylate (DMCD)) to corresponding alcohols was achieved excellently over well-dispersed MgO-supported copper catalysts (Cu/MgO), which were prepared by an alternative separate nucleation and aging step method. The characterization results revealed that the structure and catalytic performance of as-formed Cu/MgO catalysts were profoundly affected by the Cu loading. Especially, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…In this context, Mn, Fe, Co, Ni, Cu, and Zn complexes have been utilized for catalytic hydrogenation of unsaturated bonds, especially in carbonyl compounds, as modeled after a number of matured Ru complexes . In addition, (supported) metal particles based on Fe and Cu have emerged as an active area of research.…”
Section: Introductionsupporting
confidence: 89%
“…In this context, Mn, Fe, Co, Ni, Cu, and Zn complexes have been utilized for catalytic hydrogenation of unsaturated bonds, especially in carbonyl compounds, as modeled after a number of matured Ru complexes . In addition, (supported) metal particles based on Fe and Cu have emerged as an active area of research.…”
Section: Introductionsupporting
confidence: 89%
“…On the other hand, peaks at 934.2 and 954.1 eV with its shake-up peaks at 942.2 and 962.3 eV are due to the presence of Cu 2+ species 23,24 . 5d, we observe peaks at 530 and 531eV corresponding to lattice oxygen in MgO and CuO 26 , and adsorbed oxygen on the catalyst surface. 5c demonstrates the presence of Mg 1s peak at 1303.9 eV 25 .…”
Section: Resultsmentioning
confidence: 82%
“…PHI 5000 Versaprobe II X-ray 6 photoelectron spectrometer (ULVAC-PHI) using Al Kα as X-ray beam was used to understand the effect of catalysis on the oxidation states of the Cu, Mg and O components of the catalyst sample. 4d) 26,27 . Figure 4a shows peaks corresponding to Cu, Mg and O in the XPS spectrum for the sample.…”
Section: Characterizationmentioning
confidence: 99%
“…It was reported that the Cu + -Cu 0 synergy in Cu/SiO 2 catalysts could remarkably promote the extent of hydrogenation related to ester groups [19][20][21]. In addition, our groups found that the way that ester molecules interacted with Cu/MgO catalyst could be greatly influenced by the surface acid-base nature of catalysts [22]. In this regard, Cu/ ZnO and Cu/SiO 2 catalysts have been used in selective hydrogenation of DMS to GBL [23,24].…”
Section: Introductionmentioning
confidence: 93%